Scalable multi-region perimeter metering control for urban networks: A multi-agent deep reinforcement learning approach - Zhou, Dongqin; Gayah, Vikash V. (Transportation research. Part C, Emerging technologies, 2023)
•A model-free control scheme proposed for multi-region perimeter metering control•Scalability demonstrated via numerical simulations on a seven-region urban network•Learning and control efficay illustrated via comparisons to the MPC method•Resilience and transferability shown considering environment uncertainties Perimeter metering control based on macroscopic fundamental diagrams has attracted increasing research interests over the past decade. This strategy provides a convenient way to mitigate urban congestion by manipulating vehicular movements across homogeneous regions without modeling the detailed behaviors and interactions involved with individual vehicle presence. In particular, multi-region perimeter metering control holds promise for efficient traffic management in large-scale urban networks. However, most existing methods for multi-region control require knowledge of either the environment traffic dynamics or network properties (i.e., the critical accumulations), whereas such information is generally difficult to obtain and subject to significant estimation errors. The recently developed model-free techniques, on the other hand, have not yet been shown scalable or applicable to large urban networks. To fill this gap, this paper proposes a scalable model-free scheme based on multi-agent deep reinforcement learning. The proposed scheme features value function decomposition in the paradigm of centralized training with decentralized execution, coupled with critical advances of single-agent deep reinforcement learning and problem reformulation guided by domain expertise. Comprehensive experiment results on a seven-region urban network suggest the scheme is: (a) effective, with consistent convergence to final control outcomes that are comparable to the model predictive control method; (b) resilient, with superior learning and control efficacy in the presence of inaccurate input information from the environment; and (c) transferable, with sufficient implementation prospect as well as real time applicability to unencountered environments featuring increased uncertainty.